2017
DOI: 10.15604/ejef.2017.05.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of Housing Rents in Urban Albania: An Empirical Hedonic Price Application With Nsa Survey Data

Abstract: As an immobile, durable and heterogonous good, each housing unit has a bundle of different characteristics. Hedonic price method, which depends on the consumer theory of the classical economics, implies that each characteristic of heterogeneous goods provides a different level of satisfaction or utility to the consumer, being widely accepted as a toolkit for estimating effects of these characteristics on prices and rents. HPM expresses housing prices as the function of structural characteristics, location char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…This paper, like several studies in a large theoretical body of hedonic literature on residential property market (Baranzini and Schaerer, 2011; Walsh et al , 2015; Yamagata et al , 2016; Kahveci and Sabaj, 2017; Bedell, 2018; Beltrán et al , 2018; Du et al , 2018), is deeply rooted in Rosen’s (1974) work which provided a framework for hedonic analysis using a model of consumer bid and producer offer functions for determining the implicit price of the characteristics of a property for different consumers. The relationship between the price of housing units and housing attributes has been widely addressed in the coastal housing economics and property value modelling literature by the hedonic price models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This paper, like several studies in a large theoretical body of hedonic literature on residential property market (Baranzini and Schaerer, 2011; Walsh et al , 2015; Yamagata et al , 2016; Kahveci and Sabaj, 2017; Bedell, 2018; Beltrán et al , 2018; Du et al , 2018), is deeply rooted in Rosen’s (1974) work which provided a framework for hedonic analysis using a model of consumer bid and producer offer functions for determining the implicit price of the characteristics of a property for different consumers. The relationship between the price of housing units and housing attributes has been widely addressed in the coastal housing economics and property value modelling literature by the hedonic price models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generally, it has been found that housing prices tend to be higher as the area increases [25][26][27][28][29][30], and similarly, higher floors are associated with higher housing prices [3,[31][32][33][34][35]. Additionally, factors such as the number of rooms and bathrooms are frequently taken into account, and overall, it has been observed that housing prices tend to be higher with a greater number of rooms and bathrooms [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Access to subway stations, in particular, is found to increase housing prices as accessibility improves [27,28,36,52,55,56]. Moreover, some studies [18,34,38,57] argue that proximity to bus stops leads to higher housing prices. However, there is also the consistent argument that housing prices decrease in closer proximity to bus stops [30,32].…”
Section: Introductionmentioning
confidence: 99%